Feasibility study tuna leather fabric as a material for bi-fold wallets - Ebol, Shyn Marie S.
ABSTRACT From the last three decades, the leather goods industry has undergone major changes and through time the amount of the usage of leather goods has been growing due to the changes in the lifestyle and preferences of the consumers. The Philippines' fashion industry continues to explore new materials for the improvement of the industry. With these tremendous changes going on in the leather goods industry the country could take the advantage in utilizing the country's rich resources in developing innovative leather goods. This study aimed to utilize the country's rich resource in order to come up with a new material in the production of leather goods. The primary goal of the research was to determine the feasibility of tuna skin wastes as an alternative source of leather. It sought to determine the sewability property of tuna leather fabric in order to produce quality leather goods. The study was purely an experimental research that used an empirical scientific approach based on observations, measurements and practical experimentation. Through the leather tanning process, the tuna skin was proven to be a good alternative source of leather. Two types of tuna fabric were created one without finishing and the other source of leather. Two types of tuna fabric were created one without finishing and the other with glazing. Both showed excellent performance when subjected to the tear strength test and surpassed the commercial leather's standard. The study formulated sewing specifications in order to determine the sewability of the tuna leather for production of bi-fold wallets, and its sewability was confirmed through the success of the production of the wallets. In addition, both types of tuna fabric showed an outstanding result when subjected to seam strength test; but the fabric without finishing showed better results. It was concluded that the tuna leather had the following sewability property: 8 to 10 SPI Stitch length, 16 or 18 needle size, 100% polyester thread and 3 to 6 tension range. These sewing specifications were proven to be compatible to the outstanding physical fabric characteristics of the tuna leather fabric.